Leading with Meaning: Beneficiary Contact, Prosocial Impact, and the Performance Effects of Transformational Leadership - Grant, Adam M. (Academy of Management Journal, 2012)
Although transformational leadership is thought to increase followers' performance by motivating them to transcend self-interest, rhetoric alone may not be sufficient. I propose that transformational leadership is most effective in motivating followers when they interact with the beneficiaries of their work, which highlights how the vision has meaningful consequences for other people. In a quasi-experimental study, beneficiary contact strengthened the effects of transformational leadership on call center employees' sales and revenue. A survey study with government employees extended these results, supporting a moderated mediation model with perceived prosocial impact. Relational job design can enhance the motivational effects of transformational leadership.